Pemanfaatan Energi Surya Sebagai Energi Alternatif Aerator Untuk Meningkatkan Kualitas Air Kolam Ikan Hias Berukuran Kecil - Arifin, Zaenal; Saroso, Bagus Argo; Kurniawan, Agung; Ageftry, Farhan Dio (Elektrika, 2022)
Aerator has function to supply the dissolved oxygen in the water is very important for the survival of fish, therefore theaerator is required to be on for 24 hours. However, due to depending on PLN electricity, when there is a power outage for along period of time, the aerator can't supply dissolved oxygen into the pond and the oxygen supply in the pond will dropdrastically. This is dangerous because it can threaten the survival of ornamental fish. Therefore, an energy supply system isneeded that can supply electrical energy to the aerator to replace the dependency electricity from PLN. This tool is designedto use a power supply from solar panels so that it is not affected in the event of a PLN power outage, and can always supplydissolved oxygen levels for the survival of ornamental fish. In addition, this tool is also equipped with a monitoring systembased on the Nodemcu ESP8266 Microcontroller which is displayed via the Thingspeak server. The monitoring system usedin this tool uses a PH sensor and a temperature sensor. The use of PH sensors and temperature sensors because the level ofacidity (PH) and temperature are one of the parameters of water quality other than dissolved oxygen. When the aerator is on,the information on the pool water will be read through the PH sensor and temperature sensor.